Some factors affecting the Job performance level of Agricultural extension personnel to their extension duties in Dohuk and Sulaimania governorates - Al-doski, Abid A. Hasan; Laiq, Tahir M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Job performance reviews are extremely important to any organization. Through this process, the organization assesses the worthiness of all its employees. It identifies the employees who need to be trained and motivated to perform better. The Performance of extension worker, like any organizational behavior, influenced by a number of personal , economic, social and psychological variables, and some variables related to the work environment.The main objective of the study was to assess the job performance of extension personnel in Dohuk and Sulaimania governorates in Kurdistan region of Iraq as well as determine the relationships between selected personal characteristics and job performance. The sample of the research consisted of 180 respondents representing 73.2% of extension personnel working in the Agricultural Extension Centers in the two targeted governorates. A personal interview schedule was used for data collection. Percentages, mean scores, and correlation statistic were used in data analysis. The findings of the study indicate that the level of job performance for Extension workers were ranged between law and moderate in Dohuk governorate while ranged between moderate and high in Sulaimania governorate . The findings also indicated that there are a significant relationship between the job performance for Extension workers and (age, sex, years of service in extension , Job stress , participation in training courses and use of information sources) and no significant relationship between Job performance and ( level of Education ,specialization , years of practice in Agriculture work and Job satisfaction. Based on the findings of the study, The need to design policies aimed at improving the level of Job performance of Extension personnel in the targeted areas was indicated.